Engineering mechanics - Gray, Gary L.
Plesha, Gray, and Costanzo's Engineering Mechanics: Statics & Dynamics presents the fundamental concepts, clearly, in a modern context using applications and pedagogical devices that connect with today's students. The text features a four-part problem-solving methodology that is consistently used throughout all example problems. This methodology helps students lay out the steps necessary to correct problem-formulation and explains the steps needed to arrive at correct and realistic solutions. Once students have fully mastered the basic concepts, they are taught appropriate use of modern computational tools where applicable